基于有限元的传动轴受扭分析 - 钟佩思; 王景林; 刘梅; 刘凤景 (Jixie chuandong)
Based on ANSYS,FEA software,the design of drive axle is illustrated,and its stress and stiffness are cheched.Comparing the result of the hollow drive axle with the solid drives,the conclusion is drawn.Different from the conventional method,this method can describe how much and where the stress and strain is to calculate the axle’s strength precisely.